Analisis Strenght Weakness Opportunity Threat (SWOT) Dalam Menentukan Strategi Pemasaran Penjualan Roti - Dewita Sari (PRAGMATIS, 2020)
The purpose of this study is to find out and analyze the right strategy in increasing sales volume at the "Kampong Roti" bakery. The analysis used is the Strength Weakness Opportunity Threat (SWOT) analysis method. The respondents in this study were divided into two, namely the supervisor and Kampoeng Roti outlets. The sampling technique used incidental sampling with a total of 30 people. The research step, before testing, is processed using the Internal Factor Analysis (IFA) and External Factor Analysis (EFA) matrices. The results of the study based on IFA obtained a score of 3.14 and EFA obtained a score of 2.60. The mapping results show that “Kampoeng Roti” in terms of marketing occupies quadrant I (one) position. This shows that the company is able to compete or be competitive in a strong position, so that the right strategy is needed to develop its business, so that it will continue to grow or growth phase. This position must be maintained by carrying out the right marketing strategies in the form of promotion and product innovation